Validation and clinical value of the MANAGE-PD tool: A clinician-reported tool to identify Parkinson's disease patients inadequately controlled on oral medications. (November 2021) - Antonini, Angelo; Odin, Per; Schmidt, Peter; Cubillos, Fernando; Standaert, David G.; Henriksen, Tove; Jimenez-Shahed, Joohi; Alobaidi, Ali; Jalundhwala, Yash J.; Bao, Yanjun; Zamudio, Jorge; Parra, Juan Carlos; et al.
Abstract: Introduction: Making Informed Decisions to Aid Timely Management of Parkinson's Disease (MANAGE-PD) is a clinician-reported tool designed to facilitate timely identification and management of patients with advancing Parkinson's disease (PD) with suboptimal symptom control while on standard therapy. The objective of this study was to evaluate the validity and clinical value of the tool. Methods: Driven by structured inputs from a steering committee and panel of PD experts, the tool was developed to classify patients into 3 categories. Validity and clinical value were elucidated using a two-pronged approach: (i) hypothetical patient vignettes (n = 10) developed based on the MANAGE-PD tool and rated by 17 PD specialists and 400 general neurologists (GN) and (ii) patients with PD (n = 2546) managed in real-world clinical settings. Vignette validity was based on concordance between PD experts' clinical judgement and MANAGE-PD vignette categorization. Patient-level data was used for known-group comparisons (validity) and discordant pair analysis (clinical value). Results: The tool demonstrated strong validity and clinical value among PD specialists (intraclass coefficient [ICC] 0.843; Fleiss weighted kappa [ƙweighted ] 0.79) and GN (ICC 0.690; ƙweighted 0.65) using patient vignettes. MANAGE-PD also demonstrated real-world validity and clinical value based on ability to identify patients with incrementally higher clinical, economic, and humanistic PD burden across categories of the tool (p < 0.01). Conclusions: MANAGE-PD demonstrated robust validity and clinical value in identifying patients with suboptimal PD symptom control. Clinical use of MANAGE-PD may complement treatment decision-making and facilitate timely and comprehensive management of patients with advancing PD. Highlights: There is no consensus objective criteria for identifying and managing advancing PD. MANAGE-PD is a clinician tool to manage patients with PD with suboptimal PD control. MANAGE-PD demonstrated robust validity and clinical value. Clinical use of MANAGE-PD may complement clinician treatment decision-making. MANAGE-PD may facilitate timely identification and management of PD symptoms.